The EU’s Common Security and Defence Policy in the Context of European Strategic Autonomy - Molnár, Anna (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
In the wake of a worsening global security environment, the concepts of European strategic autonomy, open strategic autonomy, strategic sovereignty or the European Defence Union are becoming increasingly relevant. In addition to economic power, there has been a growing demand in recent years for the European Union (EU) to become a military power, thereby enhancing its ability to act autonomously. It is important to emphasise that these concepts cover not only the defence sector but also the fields of economy, digitalisation, and technological innovation. In this chapter, I will first briefly introduce the historical background of the Common Security and Defence Policy (CSDP). I will then provide an overview of its theoretical background by examining the concept of the European Defence Union. Following this, I will elucidate the current state of new initiatives related to European defence in connection with the accelerated integration process. Finally, I will map national defence policies regarding European strategic autonomy. As the concept of the European Defence Union has been promoted primarily by EU institutions and finds no mention in Member States’ strategic documents, the aim of the last subchapter is to analyse Member States’ perceptions regarding the concept of European strategic autonomy (EU-SA). This part of the research is based on secondary literature and an analysis of the latest national security strategic documents, particularly those of Member States. Member States have expressed diverse opinions regarding EU-SA, which was originally associated with security and defence policies. Today, it has an extended meaning that includes economic, technological and energy policies. The National Security Strategy (NSS) of one group of Member States (such as France or Italy) has prioritised EU-SA, while another group (such as the Netherlands) has developed the concept of open strategic autonomy (OSA), and the documents of a third group (such as the V4 countries) neither mention EU-SA nor OSA. The last group of Member States represents a more transatlanticist view of security and defence. Keywords: European strategic autonomy, European Defence Union, defence initiatives, security, power